Al-Qur’an dan Pengobatan Tradisional: Studi Living Qur’an Pada Masyarakat Probolinggo Jawa Timur - Abd. Basid; Lailatul Fitriyah Hadi (Universitas Islam Negeri Imam Bonjol Padang, 2022)
The Qur’an plays an important role in the life of Muslims. In daily life, Muslims cannot be separated from interaction with the Qur’an. Therefore, the interaction was well received by the community, not least in Sentulan Village, Banyuanyar District, Probolinggo Regency, East Java. The acceptance of the Sentulan Village community towards the Qur’an is manifested in a tradition, which is what Ustadz Ali Fiqri did by using the verses of the Qur’an as a medium of treatment, which later became the focus of this research. This research uses qualitative methods and is included in field research. The approach used is a phenemological approach, which aims to reveal the meaning inherent in the reception of the Qur’an by the community in Sentulan Village. Collecting data through literature and interviews with Ustadz Ali Fiqri and patients. The final results of this study indicate that the traditional treatment carried out by Ustadz Ali Fiqri in Sentulan Village, both medical and non-medical diseases, using the media of bidara leaves, coconut, turmeric, garlic, water and eggs and reading the verses of the Qur’an that then termed the verses of syifa’. The syifa’ verses in question are (Q.S. Al-Fatihah (1): 1-7, Q.S. Al-Baqarah (2): 102, Q.S. Yunus (10) 81, Q.S. Jin (72): 3, Q.S. Al-Hasyar (59): 21, Q.S. Al-Syu’ara’ (26): 51, and Q.S. Yasin (36)).